Alias Alejandro y Sibila, retrato familiar del conflicto armado interno en el Perú - Godoy, Mauricio (2017)
Among the political documentary cinema in Latin America, Peru documentary has been focused in its internal conflict since the last fifteen years. This subject has been on the core of different analysis and publications. However, the subjective turn has not been taking importance along these works. In this article the author discusses about the importance on the subjectivity through the analysis of the films Alias Alejandro (Cárdenas, 2005) and Sibila (Arredondo, 2012), in which ones with an autobiographical approach results in a complex final product, taking distance of the apparent “truth” representations mainly boarded by classical documentaries films.